2022
DOI: 10.1186/s12886-022-02481-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-335 promotes corneal neovascularization by Targeting EGFR

Abstract: Background Corneal neovascularization (CRNV) is a severe threat to the vision of people. MicroRNA-335 (miR-335) has the function of facilitating angiogenesis. However, whether miR-335 regulates the progression of CRNV remains unclear. Methods The miR-335 expressions in CRNV rats induced by corneal suture and HUVECs induced by b-FGF were detected by quantitative real-time PCR. For the miR-335 function, wound healing and tube formation assays were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Both human and animal studies have identified miRNAs within the cornea which regulate a variety of homeostatic processes including cell differentiation [88], proliferation [89], migration [90], apoptosis [91] and SC maintenance [88]. They can also modulate pathophysiological processes including corneal wound healing [90,[92][93][94][95], neovascularization [96,97], inflammation [98] and immune defense [99,100]. Reports of differential miRNA expression across anatomically distinct ocular surface regions, such as corneal, limbal and conjunctival compartments [101][102][103], suggests that targeting specific miRNAs may serve as amenable therapeutic options for correcting ocular defects.…”
Section: Differential Microrna Expression In the Diabetic Limbusmentioning
confidence: 99%
“…Both human and animal studies have identified miRNAs within the cornea which regulate a variety of homeostatic processes including cell differentiation [88], proliferation [89], migration [90], apoptosis [91] and SC maintenance [88]. They can also modulate pathophysiological processes including corneal wound healing [90,[92][93][94][95], neovascularization [96,97], inflammation [98] and immune defense [99,100]. Reports of differential miRNA expression across anatomically distinct ocular surface regions, such as corneal, limbal and conjunctival compartments [101][102][103], suggests that targeting specific miRNAs may serve as amenable therapeutic options for correcting ocular defects.…”
Section: Differential Microrna Expression In the Diabetic Limbusmentioning
confidence: 99%